ISLAMIC UNIT LINKED: IS IT PROFITABLE AND FULLY SHARIA COMPLIANCE? - Kholis, Nur (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2016)
Islamic Unit Linked: Is It Profitable and Fully Sharia Complience? Recently the interest of society to choose unit linked Islamic or conventional as an instrument for investment rises significantly. It is maybe because of its impressive tagline, combination between investment and protection. At glance, unit linked provide veryeasy way to invest. At the same time, customer will receive many pieces of papers describe rules dan regulations that make customer confused and do not understand how much cost must be paid for purchasing unit linked. The objective of this study is to review whether Islamic unit linked is profitable investment? Does the operationof practical Islamic unit link fully comply with sharia rules? Based on analysis conducted, not all Islamic unit link offered is profitable and fully with sharia compliance. Therefore, it is suggested to the investors should consider some aspects before deciding any investment in Islamic unit link